Application of the Exactive Plus EMR for automated protein–ligand screening by non‐covalent mass spectrometry. (15th July 2014) - Maple, Hannah J.; Scheibner, Olaf; Baumert, Mark; Allen, Mark; Taylor, Richard J.; Garlish, Rachel A.; Bromirski, Maciej; Burnley, Rebecca J.
<x xml:space="preserve">Abstract</x> RATIONALE Non‐covalent mass spectrometry (MS) offers considerable potential for protein‐ligand screening in drug discovery programmes. However, there are some limitations with the time‐of‐flight (TOF) instrumentation typically employed that restrict the application of non‐covalent MS in industrial laboratories. METHODS An Exactive Plus EMR mass spectrometer was investigated for its ability to characterise non‐covalent protein–small molecule interactions. Nano‐electrospray ionisation (nanoESI) infusion was achieved with a TriVersa NanoMate. The transport multipole and ion lens voltages, dissociation energies and pressure in the Orbitrap™ were optimised. Native MS was performed, with ligand titrations to judge retention of protein‐ligand interactions, serial dilutions of native proteins as an indication of sensitivity, and a heterogeneous protein analysed for spectral resolution. RESULTS Interactions between native proteins and ligands are preserved during analysis on the Exactive Plus EMR, with the binding affinities determined in good agreement with expected values. High spectral resolution allows baseline separation of adduct ions, which should improve the accuracy and limit of detection for measuring ligand interactions. Data are also presented showing baseline resolution of glycoforms of a highly glycosylated protein, allowing binding of a fragment molecule to be detected. CONCLUSIONS The high sensitivity and spectral resolution achievable with the Orbitrap technology confer significant advantages over TOF mass spectrometers, and offer a solution to current limitations regarding throughput, data analysis and sample requirements. A further benefit of improved spectral resolution is the possibility of using heterogeneous protein samples such as glycoproteins for fragment screening. This would significantly expand the scope of applicability of non‐covalent MS in the pharmaceutical and other industries. Copyright © 2014 John Wiley & Sons, Ltd.